MICROALGAE – BIODIESEL POTENTIAL PRODUCERS: A REVIEW - Anna Krasowska; Slawomir Jablonski; Piotr Biniarz; Malgorzata Plachetka; Marcin Lukaszewicz (European Scientific Journal, ESJ, 2013)
Declining quantity of fossil fuels force scientific community to think about alternative energy sources. Thus, it is critical to focus on renewable resources and development of new technologies. Solar energy seems to be sufficient for actual energy demand. The question is what is the most efficient method for its capture, storage and distribution. As diesel stands for the third part of fossil fuels used in transport, cultivation of microalgae and extraction of lipids out of cells is one of the possibilities. Biodiesel produced from microalgae-derived lipids offers notable environmental benefits e.g. reducing the greenhouse effect by utilization of CO2 emissions or sewage treatment. The review includes descriptions of species selection for biodiesel production, genetic modifications leading for to higher efficiency and production process improvement, biomass and metabolites recovery from cultures, transestrification process leading to biodiesel, waste utilization and business value. Microalgae can potentially offer substantially higher yields than other oil-producing crops and they can grow beside fresh water also in saline water or even sewage. Additionally microalgae do not compete with productive farmland thus there is no competition with food chain. In spite of many advantages of biodiesel production from algae, there are a lot of limitations blocking its real competition with petrodiesel. Production costs seem the most substantial problem. Out of all recognized methods of microalgae production, the culture of microalgae in photobiopanels seems the most favorable for biodiesel production, however the costs are discouraging. Probably small modular systems may be an attractive solution with positive economical rationale.